Acid-free synthesis of oxygen-enriched electroactive carbon with unique square pores from salted seaweed for robust supercapacitor with attractive energy density. Issue 21 (15th October 2018) - Xue, Chunfeng; Feng, Lin; Hao, Yanan; Yang, Fujuan; Zhang, Qian; Ma, Xuli; Hao, Xiaogang
Abstract : Oxygen-enriched electroactive carbon with unique square pores is prepared by carbonizing salted seaweed and shows high energy density in electric double-layer capacitors. Abstract : Oxygen-enriched porous electroactive carbon (OPEC) is prepared by simply carbonizing salted seaweed and only washing with water. The recrystallized NaCl cube is chemically stable and mainly acts as a pore filler in the pristine seaweed. It helps to maintain the innate pore system and simultaneously templates the formation of square pores. Its shielding effect not only enhances the onset decomposition temperature but also helps to achieve high yield. It can also be completely removed by washing with the green solvent water. The obtained OPEC-800 material not only shows a specific surface area of 329.3 m 2 g −1 but also a microporous structure (0.8–2.0 nm) matching with the electrolyte 1.0 M H2 SO4 . It exhibits a specific capacitance of 324.3 F g −1 (specific surface-area capacitance is 98.5 μF cm −2 ) at a current density of 0.50 A g −1 in a three-electrode system. Its high oxygen content of 19.1% can lead to a wide operating voltage window of 0.0–1.40 V and an attractive energy density of 15.9 W h kg −1 at a power density of 175.0 W kg −1 in a two-electrode system. Furthermore, it also displays an excellent cyclic stability (98%, 10 000 cycles) and good rate performance. The whole process is a green, oxidant-free, acid-free, and low-cost method for converting green biomass into self-functionalized carbon with naturally connected pores aiming to fabricate green energy devices. All the attractive features make the environmentally friendly route a competitive candidate for preparing other porous electroactive materials.